2009
DOI: 10.5194/acp-9-4011-2009
|View full text |Cite
|
Sign up to set email alerts
|

Taklimakan dust aerosol radiative heating derived from CALIPSO observations using the Fu-Liou radiation model with CERES constraints

Abstract: Abstract. The dust aerosol radiative forcing and heating rate over the Taklimakan Desert in Northwestern China in July 2006 are estimated using the Fu-Liou radiative transfer model along with satellite observations. The vertical distributions of the dust aerosol extinction coefficient are derived from the CALIPSO (Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations) lidar measurements. The CERES (Cloud and the Earth's Energy Budget Scanner) measurements of reflected solar radiation are used to c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
145
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 257 publications
(159 citation statements)
references
References 44 publications
14
145
0
Order By: Relevance
“…The area-averaged radiative forcing of dust over the entire domain is summarized in Table 4. By simple comparison of values in Table 4, we can conclude that a quarter to one-third of the SW radiative forcing is counterbalanced by LW radiative effects, which is consistent with a previous study (Huang et al, 2009). Figure 12 shows the ensemble means of cloud fraction responses (ALLF minus NDST) between various atmospheric layers to Middle East dust aerosols in JJA 2008.…”
Section: Radiative Effect Of Dustsupporting
confidence: 76%
“…The area-averaged radiative forcing of dust over the entire domain is summarized in Table 4. By simple comparison of values in Table 4, we can conclude that a quarter to one-third of the SW radiative forcing is counterbalanced by LW radiative effects, which is consistent with a previous study (Huang et al, 2009). Figure 12 shows the ensemble means of cloud fraction responses (ALLF minus NDST) between various atmospheric layers to Middle East dust aerosols in JJA 2008.…”
Section: Radiative Effect Of Dustsupporting
confidence: 76%
“…Both the AOD and AAI comparisons suggest that transported natural dust plays an important role in differentiating between the regions, although local aerosols are also quite different between the regions. Huang et al (2009) found that the single scattering albedo (SSA) of Taklamakan dust aerosols is about 0.89 at 0.67 µm which is about 6% less than for Saharan dust. Ge et al (2010) also confirmed that the SSA shows an increasing trend with wavelength, indicating stronger dust aerosol absorption at shorter wavelengths.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Iwasaka et al, 2003;Yamada et al, 2005;Shen et al, 2006;Huang et al, 2009;Liu et al, 2002a). However few observations were carried out over the semiarid region of the Loess Plateau.…”
Section: Introductionmentioning
confidence: 99%